2018
DOI: 10.1161/jaha.118.009544
|View full text |Cite
|
Sign up to set email alerts
|

Ideal Cardiovascular Health and Biomarkers of Subclinical Brain Aging: The Northern Manhattan Study

Abstract: BackgroundThe American Heart Association Life's Simple 7 metric defines ideal cardiovascular health (CVH) on 7 factors: smoking, diet, physical activity, body mass index, blood sugar, blood pressure, and cholesterol. This metric has been used to define optimal brain health, but data relative to subclinical imaging biomarkers of brain aging are lacking. This study examines the association between Life's Simple 7 with white matter hyperintensity volume, silent brain infarcts, and cerebral volume.Methods and Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
18
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 26 publications
7
18
1
Order By: Relevance
“…We found no association with cardiovascular health, which is consistent with some but not all previous studies 1032 33 35 The large heterogeneity in population settings (mean age ranged from young adulthood to older age), as well as the type of brain imaging analysis, might explain inconsistent findings. Further investigations are thus needed to confirm specific brain correlates of cardiovascular health.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…We found no association with cardiovascular health, which is consistent with some but not all previous studies 1032 33 35 The large heterogeneity in population settings (mean age ranged from young adulthood to older age), as well as the type of brain imaging analysis, might explain inconsistent findings. Further investigations are thus needed to confirm specific brain correlates of cardiovascular health.…”
Section: Discussionsupporting
confidence: 89%
“…26 32 33 Cardiovascular health has been shown to be associated with whole brain volume,10 32 although findings on specific markers are less consistent 1026 32 33 White matter hyperintensities, particularly in the deep white matter, are usually interpreted as “microvascular changes” that are associated with vascular risk in general 34. We found no association with cardiovascular health, which is consistent with some but not all previous studies 10…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The extremely low ideal CVHS (1%) and high poor CVHS (90%) among CWP with a mean age of 44 years seen in our study are very alarming, although our observed ideal CVHS is somewhat better than that reported in previous studies [ 15 , 16 ]. The younger age, medical education and health care profession in CWP may explain the differences regarding the number of subjects with ≥ 2 risk factors and CVHS healthy factor score between CWP and NPC.…”
Section: Discussioncontrasting
confidence: 80%
“…The poor levels (as risk factors) of CVH metrics, especially occurring from midlife, are supposed to contribute mainly to macro-and microvascular lesions and neurodegenerative process in the brain, e.g., oxidative stress, inflammation, atherosclerosis, hypoxia, cerebral small vessel lesions, and advanced glycation end products [36]. Optimal or ideal levels of CVH metrics (e.g., no smoking, physical activity, and normal blood glucose) are associated with less burden of cerebrovascular damage [37], which then leads to fewer white matter lesions and brain infarcts as well as less severe neurodegeneration [2,38]. The optimal brain health resulting from optimal CVH profiles may in turn contribute to the lower risk of cognitive impairment [39] and cognitive decline [17,18], and thus lead to a lower risk of dementia.…”
Section: Discussionmentioning
confidence: 99%